An Analysis of Local and Target Culture Integration in English Textbooks - Sorongan, Dian Anggraini; Susanti, Rini; Syahri, Indawan (LINGUA: Jurnal Bahasa dan Sastra, 2014)
This study aimed to find out the percentage of local culture integration and target culture integration in the selected English textbooks for senior high school âEnglish Zoneâ and âInterlanguageâ. This research design was a content analysis with 1487 paragraphs and 638 pictures as the study data. The procedure of analyzing the data started by classifying the data into local or target culture division then it was analyzed based on Byrams cultural content checklist (1993) while the pictures were simply classified into local culture or target culture. The result of the analysis was made in the form of percentage. The results show that for analysis of the paragraph, the percentage of local culture integration in English Zone is 31,23 % and in Interlanguage is 9,6 % meanwhile the percentage of target culture integration in English Zone is 10,17% and in Interlanguage is 11,02%. For the picture analysis, the percentage of local culture integration in English Zone is 6,43 % and in Interlanguage is 18,2% meanwhile the percentage of target culture integration in English Zone is 12,41% and in Interlanguage is 20 %.